A Homozygous Deep Intronic Mutation Alters the Splicing of Nebulin Gene in a Patient With Nemaline Myopathy - Laflamme, Nathalie; Lace, Baiba; Thonta Setty, Samarth; Rioux, Nadie; Labrie, Yvan; Droit, Arnaud; Chrestian, Nicolas; Rivest, Serge (Frontiers in Neurology, 2021)
Nemaline myopathy is a rare disorder affecting the muscle sarcomere. Mutations in Nebulin gene (NEB) are known to be responsible for about 50% of the Nemaline myopathy cases. Nebulin is a giant protein which formed integrally with the sarcomeric thin filament. This complex gene is subject to extensive alternative splicing giving rise to multiple isoforms. In this study, we have recruited a six years old boy presenting with general muscular weakness. Identification of rods-shape structures in the patient’ biopsy raised doubt about the presence of a nemaline myopathy. Next generation sequencing was used to identify a causative mutation for the patient syndrome. A deep intronic substitution was found in the intron 144 of the NEB. The variant is predicted by in silico tools to create a new donor splice site. Molecular analysis showed that the mutation could alter splicing events of the Nebulin leading to significant decrease of several isoforms. This change in the expression level of the isoforms could give rise to functional consequences in the sarcomere. These results are consistent with the phenotypes observed in the patient. Discovery of variants in this gene would allow a better understanding of the Nebulin involvement in neuromuscular disease and maybe allow progress in the research for nemaline myopathy treatment.